Laboratory friction testing of cross-country skis: Experimental investigation of ski design parameters` effect on friction - Auganæs, S. B. (Norwegian University of Science and Technology, 2024)
Cross-country skiing holds a significant place in Norway's cultural history as the national sport. It plays a crucial role both in public health as a recreational activity and as a highly competitive sport. A decisive factor for performance in cross-country skiing is the friction between the ski and snow. As a consequence, a lot of effort is put into developing fast skis and glide products. In this development process, glide testing is essential to distinguish small differences between the products. However, a significant influence of changing weather, snow conditions and skier position make this task challenging in the field. This has made researchers develop laboratory setups to better control external factors. However, to obtain stable measurements, simplifications have been made by substituting snow with ice, and reducing both the sample size and speed. Therefore, the primary objective of this thesis has been to examine the friction between skis and snow within a controlled environment, under conditions that apply to crosscountry skiing. The first part of this work consisted of the development of a ski-snow tribometer (an instrument for measuring friction). This tribometer comprises a 6.5-meter-long snow track situated inside a freezing chamber. A ski is mounted to a carriage, which is driven across the track while the normal- and frictional forces are measured. Additionally, laboratory-grown dendritic snow has been produced by a custom-built snow machine as part of this setup. The results from the precision investigation showed that the setup could measure the friction coefficient of skis on new dendritic snow with a precision good enough to distinguish skis or glide products with very similar performance (?µ = 0.001). Based on the insights from the first study a new method to test skis has been developed. This method reduces the impact of a constantly changing snow surface with repeated runs, on the measured coefficient of friction. By assuming a linear polishing/friction trend of the measured coefficients of friction, the data can be modified to remove the effect of a falling or rising trend. This approach has proven effective in mitigating the impact of a changing coefficient of friction on the average between the skis and has been used in subsequent experimental studies.